EVALUASI PELAKSANAAN PROGRAM GURU PENGGERAK TERHADAP PENINGKATAN KUALITAS PEMBELAJARAN DI SD INPRES PANGKABINANGA KECAMATAN PALLANGGA KABUPATEN GOWA - Suriyani Supriadi; Widya Karmila Sari Achmad, Nurhaedah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the implementation of the Teacher Driving Program (Guru Penggerak) in improving the quality of learning at SD Inpres Pangkabinanga, Pallangga District, Gowa Regency. The Teacher Driving Program is a strategic initiative to enhance teachers competence and professionalism as learning leaders, agents of change, and drivers of the educational ecosystem in elementary schools. This research employs a qualitative approach using the CIPP evaluation model (Context, Input, Process, Product). Data were collected through observation, interviews, and document analysis involving teacher drivers, fellow teachers, students, and school stakeholders. The research results are expected to provide a comprehensive overview of the effectiveness of the Teacher Driving Program in improving learning quality and offer recommendations for future program development. The findings are anticipated to serve as a reference for policymakers and education practitioners in efforts to improve the quality of education at the elementary school level.